The Development of Industrial Work Practice Monitoring by Using “Simorin” at Vocational High School (Journal of Vocational and Career Education, 2017)
Vocational High School graduates are expected to have work experience in industry and ready to enter the workforce. Industrial work practice (Prakerin) is a learning program that must be implemented by students in the industrial world. Prakerin program is organized together between school and the world of work to meet the students' need for competencies that are unworkable in schools. There are still major obstacles in monitoring the implementation of Prakerin due to distance and time problems. These constraints are expected to be solved using information system.This research and development aims to produce an effective and effective information system on industrial work practice monitoring to be used in vocational high school. This study developed information system named "Simorin" which is an acronym of the Industrial Work Practice Monitoring Information System. The method used in the study was research and development (R D). Stages in this study included analysis phase, data requirement by using literature study and field study. The test phase was performed with validation and revision followed by a limited trial of Simorin products.Based on the development, test and analysis, it can be concluded that Simorin was feasible and effective for use in Prakerin monitoring process in terms of usability. Students, Teachers and industries could communicate with each other in real time. Recommendation of further development of Simorin is that it can be integrated with distance learning (e-learning).